Antibacterial foam dressing and composite layer thereof
By mixing UiO-66-(SH)2@TCPP@AgNPs powder with polyurethane dimethyl sulfoxide solution, an antibacterial composite layer was prepared, which solved the problem of traditional foam dressings lacking antibacterial and promoting healing ability, achieving efficient absorption of leucorrhea and antibacterial effects, and promoting wound healing.
Patent Information
- Application Number
- CN202411867006.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-11
AI Technical Summary
Traditional polyurethane foam dressings lack antibacterial and bactericidal ability, poor healing ability, and long-term use of antibiotic liquids may lead to human drug resistance.
The dimethyl sulfoxide solution of polyurethane was mixed with UiO-66-(SH)2@TCPP@AgNPs powder, and the composite layer was prepared by freeze-drying method to form an antibacterial foam dressing. The composite layer consists of a polyurethane film layer, a composite layer, a medical pressure-sensitive adhesive layer and a release layer, and has strong liquid absorption and oozing ability and antibacterial properties.
It enhances the ability of foam dressing to absorb ooze, has antibacterial properties, promotes cell proliferation, accelerates wound healing, and avoids secondary reflux of ooze, improving the safety and effect of the dressing.
Smart Images

Figure CN119587739A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical dressings, and in particular relates to an antibacterial foam dressing and a composite layer thereof. Background Art
[0002] Polyurethane foam dressings are used to cover wounds and absorb wound exudate. The surface and interior of the polyurethane foam pad are densely covered with openings. The fine openings on the surface can quickly absorb liquid, and the coarse openings inside can store a large amount of liquid, thereby absorbing wound exudate and maintaining a certain humidity on the wound. The composite superabsorbent pad has strong water absorption. After being compounded with the polyurethane foam layer, the exudate can be absorbed by the foam layer, transported vertically upward, and locked in the exudate, which will not cause secondary reflux of the exudate.
[0003] The shortcomings of traditional polyurethane foam dressings are: first, traditional foam dressings only have the ability to cover the wound and absorb wound exudate, and do not have antibacterial and bactericidal effects; second, the ability of foam dressings to promote healing comes from absorbing exudate and providing a comfortable environment for the wound, and its ability to promote healing is poor; third, most of the antibacterial foam dressings currently available use antibiotics and other antibacterial liquids, and long-term use will cause drug resistance in the human body. Summary of the invention
[0004] The object of the present invention is to provide an antibacterial foam dressing to solve the deficiencies of conventional polyurethane foam in the prior art; the object of the present invention is also to provide a composite layer used in the above antibacterial foam dressing.
[0005] To achieve the above purpose, a composite layer of the present invention adopts the following technical solution: A composite layer is prepared by uniformly mixing a polyurethane dimethyl sulfoxide solution with UiO-66-(SH)2@TCPP@AgNPs powder and then freeze-drying, wherein the mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 400:1-100:1, the mass fraction of the polyurethane in the polyurethane dimethyl sulfoxide solution is 5%-20%, and vertical directional freezing is performed during freeze-drying.
[0006] Furthermore, the mass fraction of polyurethane in the dimethyl sulfoxide solution of polyurethane is 10%.
[0007] Furthermore, when the polyurethane dimethyl sulfoxide solution is mixed with the UiO-66-(SH)2@TCPP@AgNPs powder, the mixture is first stirred and then placed in an ultrasonic disperser for dispersion, so that the UiO-66-(SH)2@TCPP@AgNPs powder is fully dispersed.
[0008] Furthermore, the mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 200:1.
[0009] An antibacterial foam dressing of the present invention adopts the following technical solution: An antibacterial foam dressing comprises, from outside to inside, a polyurethane film layer, a composite layer, a medical pressure-sensitive adhesive layer and a release layer. The composite layer is prepared by evenly mixing a polyurethane dimethyl sulfoxide solution with UiO-66-(SH)2@TCPP@AgNPs powder and subjecting the mixture to freeze-drying. The mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 400:1-100:1, the mass fraction of the polyurethane in the polyurethane dimethyl sulfoxide solution is 5%-20%, and vertical directional freezing is performed during freeze-drying.
[0010] Furthermore, the mass fraction of polyurethane in the dimethyl sulfoxide solution of polyurethane is 10%.
[0011] Furthermore, when the polyurethane dimethyl sulfoxide solution is mixed with the UiO-66-(SH)2@TCPP@AgNPs powder, the mixture is first stirred and then placed in an ultrasonic disperser for dispersion, so that the UiO-66-(SH)2@TCPP@AgNPs powder is fully dispersed.
[0012] Furthermore, the mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 200:1.
[0013] Furthermore, a super absorbent fiber layer is provided between the polyurethane film layer and the composite layer.
[0014] Furthermore, the thickness of the super absorbent fiber layer is 2mm-3mm.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. After the metal organic framework material is introduced into the polyurethane foam layer, the ability of the foam dressing to absorb exudate is enhanced.
[0016] 2. The metal organic framework contains silver ions, and the bactericidal properties of the silver ions themselves make the foam dressing antibacterial.
[0017] 3. The polyurethane foam layer is prepared by directional freeze-drying, which not only makes the metal organic framework material more evenly distributed in the polyurethane foam and makes the two more closely connected, but also introduces directional hollow channels into the polyurethane foam layer, thereby increasing its specific surface area and further increasing the liquid absorption capacity of the dressing. At the same time, it also enhances the liquid conduction capacity of the composite layer, and cooperates with the super absorbent fiber layer to prevent the exudate from flowing back to soak the wound for a second time.
[0018] 4. It can promote cell proliferation and accelerate wound healing under light.
[0019] The parts not involved in the device are the same as the existing technology or can be implemented by using the existing technology. The structure of the invention is scientific and reasonable, and it is safe and convenient to use, which provides great help to people. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiment 1 of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 This is an electron microscope image of a vertical section of a composite layer in Example 1 of an antibacterial foam dressing of the present invention; Figure 2 is an electron microscope image of a cross section of a composite layer in Example 1 of an antibacterial foam dressing of the present invention; Figure 3 is a comparison chart of the amount of liquid absorbed by the super absorbent fiber layer in the foam dressing prepared in Example 1 of the present invention and Comparative Example 1; Figure 4 It is a comparison chart of the amount of liquid absorbed by the upper and lower surfaces of the foam dressings prepared in Example 1 of the present invention and Comparative Example 1; Figure 5 is the survival rate of cells when the foam dressings prepared in Example 1 and Comparative Example 2 of the present invention are used in a cell survival experiment; Figure 6 is a comparison chart of the liquid absorption of the composite layer prepared in Example 1 of the present invention and the comparative example; Figure 7 The present invention is a schematic structural diagram of an antibacterial foam dressing. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1 of an antibacterial foam dressing of the present invention: An antibacterial foam dressing, with the side facing away from the skin as the outer side and the side contacting the skin as the inner side, comprises, from the outside to the inside, a polyurethane film layer 1, a super absorbent fiber layer 2, a composite layer 3, a medical pressure-sensitive adhesive layer 4 and a release layer 5.
[0023] The medical pressure-sensitive adhesive layer 4 can fix the dressing on the skin surface well, and will not cause strain to the skin when changing the dressing. The composite layer 3 is a mixture of polyurethane foam and metal organic framework material (UiO-66-(SH)2TCPPAgNPs powder), which has a strong ability to absorb exudate and can promote cell proliferation under light conditions. The super absorbent fiber layer 2 can absorb the exudate absorbed by the composite layer, move it upward to the fiber layer, and lock the exudate so that the exudate will not flow back to soak the wound. The super absorbent fiber is an existing material and will not be introduced in detail in this application. The backing adopts a polyurethane film layer 1, which is a colorless and transparent film. It not only plays a waterproof role, but also its colorless and transparent properties allow light to penetrate the film and irradiate the composite layer, so that the organic metal framework material can play its ability to promote cell proliferation.
[0024] The thickness of the super absorbent fiber layer 2 is 2 mm to 3 mm to avoid shading.
[0025] The preparation method of the composite layer 3 is as follows: In the first step, 10 wt% polyurethane dimethyl sulfoxide solution and UiO-66-(SH)2@TCPP@AgNPs powder were prepared respectively; The method for preparing a 10 wt % polyurethane dimethyl sulfoxide solution is as follows: 10 g of polyurethane is taken, put into 90 g of dimethyl sulfoxide (DMSO), and stirred at 80° C. until the polyurethane is completely dissolved.
[0026] The preparation of UiO-66-(SH)2@TCPP@AgNPs powder belongs to the prior art and will not be described in detail in this application.
[0027] In the second step, 0.5 g of UiO-66-(SH)2@TCPP@AgNPs powder was dispersed in 100 g of polyurethane solution to obtain a mixture; Specifically, 0.5 g of UiO-66-(SH)2@TCPP@AgNPs powder was poured into the 10 wt% polyurethane dimethyl sulfoxide solution prepared in the first step, stirred for 60 min, and then placed in an ultrasonic disperser for 30 min to fully disperse the UiO-66-(SH)2@TCPP@AgNPs powder in the polyurethane solution to obtain a mixture.
[0028] In the third step, the dispersed mixture is poured into a mold, the composite layer is prepared using freeze-drying method, and then cut into appropriate sizes.
[0029] Specifically, the mold is placed in a freeze dryer for directional freezing. After no liquid flows in the mold, the mold is removed, the solid is placed in the freeze dryer, the vacuum pump is turned on, and the composite layer is obtained after freeze drying for 48 hours.
[0030] Embodiment 2 of an antibacterial foam dressing of the present invention: The difference between Example 2 and Example 1 is that the preparation method of the composite layer 3 is different. The specific preparation method of the composite layer 3 in this example is as follows: In the first step, 5 wt% polyurethane dimethyl sulfoxide solution and UiO-66-(SH)2@TCPP@AgNPs powder were prepared respectively; The method for preparing a 5 wt % polyurethane dimethyl sulfoxide solution is as follows: 5 g of polyurethane is put into 95 g of dimethyl sulfoxide (DMSO), and stirred at 80° C. until the polyurethane is completely dissolved.
[0031] The preparation of UiO-66-(SH)2@TCPP@AgNPs powder belongs to the prior art and will not be described in detail in this application.
[0032] In the second step, 0.25 g of UiO-66-(SH)2@TCPP@AgNPs powder was dispersed in 100 g of polyurethane solution to obtain a mixture; Specifically, 0.1 g of UiO-66-(SH)2@TCPP@AgNPs powder was poured into the 10 wt% polyurethane dimethyl sulfoxide solution prepared in the first step, stirred for 50 min, and then placed in an ultrasonic disperser for 30 min to fully disperse the UiO-66-(SH)2@TCPP@AgNPs powder in the polyurethane solution to obtain a mixture.
[0033] In the third step, the dispersed mixture is poured into a mold, the composite layer is prepared using freeze-drying method, and then cut into appropriate sizes.
[0034] Specifically, the mold is placed in a freeze dryer for directional freezing. After no liquid flows in the mold, the mold is removed, the solid is placed in the freeze dryer, the vacuum pump is turned on, and the composite layer is obtained after freeze drying for 48 hours.
[0035] Embodiment 3 of an antibacterial foam dressing of the present invention: The difference between Example 3 and Example 1 is that the preparation method of the composite layer 3 is different. The specific preparation method of the composite layer 3 in this example is as follows: In the first step, 20 wt% polyurethane dimethyl sulfoxide solution and UiO-66-(SH)2@TCPP@AgNPs powder were prepared respectively; The method for preparing a 20 wt % polyurethane dimethyl sulfoxide solution is as follows: 20 g of polyurethane is taken, put into 80 g of dimethyl sulfoxide (DMSO), and stirred at 80° C. until the polyurethane is completely dissolved.
[0036] The preparation of UiO-66-(SH)2@TCPP@AgNPs powder belongs to the prior art and will not be described in detail in this application.
[0037] In the second step, 1 g of UiO-66-(SH)2@TCPP@AgNPs powder was dispersed in 100 g of polyurethane solution to obtain a mixture; Specifically, 1 g of UiO-66-(SH)2@TCPP@AgNPs powder was poured into the 10 wt% polyurethane dimethyl sulfoxide solution prepared in the first step, stirred for 50 min, and then placed in an ultrasonic disperser for 30 min to fully disperse the UiO-66-(SH)2@TCPP@AgNPs powder in the polyurethane solution to obtain a mixture.
[0038] In the third step, the dispersed mixture is poured into a mold, the composite layer is prepared using freeze-drying method, and then cut into appropriate sizes.
[0039] Specifically, the mold is placed in a freeze dryer for directional freezing. After no liquid flows in the mold, the mold is removed, the solid is placed in the freeze dryer, the vacuum pump is turned on, and the composite layer is obtained after freeze drying for 48 hours.
[0040] Take the composite layers prepared in Example 1, Example 2 and Example 3 as samples, weigh the mass W9 of the composite layers of Example 1, Example 2 and Example 3 respectively, add purified water to the beaker, weigh the mass W10 of the beaker and the purified water at this time, add the composite layer to the beaker, wait for it to be saturated with water, take out the composite layer, weigh the mass W11 of the beaker and the purified water at this time, the liquid absorption amount of the composite layer per unit mass = (W10-W11) / W9.
[0041] Take the above-mentioned saturated absorption composite layer, whose mass is W12=(W10-W11)+W9, and place it on a plane. Use a flat plate weighing 5g and place it on top of the composite layer. Let it stand for 20 minutes. After absorbing the surrounding seepage, weigh the mass of the composite layer at this time as W13.
[0042] 100 bacteria were placed in a bacterial culture medium, and four culture mediums were prepared for use. The composite layers of Example 1, Example 2, and Example 3 were taken out and cut into 5 mm pieces. The pieces were added to three of the culture mediums, and the other culture medium was used as a control group without composite layer pieces. After culturing for 24 hours, the survival of the bacteria was observed. The sterilization efficiency was (100-number of surviving cells)%.
[0043] The liquid absorption amount and liquid exudation amount of the composite layer per unit mass in Examples 1-3, and the bactericidal efficiency of the composite layer per unit mass in Examples 1-3 and the comparative example are shown in Table 1.
[0044] Table 1 Comparison table of liquid absorption, liquid exudation and sterilization efficiency of composite layer per unit mass sample Liquid absorption g / g Liquid exudate g Sterilization efficiency% Example 1 22.8 3.5 95 Example 2 22.2 6.4 83 Example 3 20.3 2.8 96 Control group 0 It can be seen from Table 1 that with the increase of the mass fraction of polyurethane in the dimethyl sulfoxide solution of polyurethane, the liquid absorption of the composite layer will first increase and then decrease, and when the mass fraction of polyurethane increases, the liquid absorption of the composite layer decreases significantly. This is because when the mass fraction of the polyurethane dimethyl sulfoxide solution is large, the polyurethane is difficult to dissolve, and the obtained polyurethane foam layer has fewer internal pores and smaller pore size, which is not conducive to liquid absorption.
[0045] At the same time, as the mass fraction of polyurethane in the dimethyl sulfoxide solution of polyurethane decreases, the amount of liquid exudation under pressure increases. This is because when the mass fraction of polyurethane decreases, the mechanical properties of the freeze-dried composite layer will deteriorate, specifically, the deformation of the composite layer increases and the elasticity decreases when subjected to external force.
[0046] As shown in Table 1, as the mass ratio of polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs powder increases, the sterilization efficiency of the composite layer will increase. When the mass ratio of the two exceeds 200:1, the sterilization efficiency is not significantly improved when the mass proportion of UiO-66-(SH)2@TCPP@AgNPs powder is increased. And when the amount of UiO-66-(SH)2@TCPP@AgNPs powder added is increased, the cost will increase significantly.
[0047] Comparative Example 1: The shape and structure of the antibacterial foam dressing in Comparative Example 1 are the same as those in Example 1, and the only difference is the preparation method of the composite layer. The preparation method of the composite layer in Comparative Example 1 is as follows: In the first step, 10 g of waterborne polyurethane prepolymer, 0.3 g of silicone oil, 0.2 g of N,N-dimethylcyclohexane, 0.3 g of n-pentane, 0.5 g of UiO-66-(SH)2@TCPP@AgNPs, and 13 g of purified water were added into a beaker and stirred at 3000 r / min for 10 min to prepare a foaming solution.
[0048] In the second step, 13 g of isocyanate was added to the foaming solution, and stirring was continued at 1000 rpm-1200 rpm for 6 minutes. Then, the foaming solution was placed in a foaming mold and kept warm at 60°C for 1 hour. After the foaming was completed, the solution was demoulded and cut to obtain a composite layer.
[0049] The polyurethane dimethyl sulfoxide solution in Example 1 is polyurethane directly dissolved in dimethyl sulfoxide solvent. After freeze-drying, the main component of the polyurethane foam layer produced is polyurethane; the silicone oil, cyclohexane, n-pentane, etc. in Comparative Example 1 do not participate in the actual chemical reaction, and isocyanate serves as a foaming agent, which only changes the shape of the polyurethane chain after polymerization and has no effect on the polyurethane itself. Therefore, the content of polyurethane, the main component of the polyurethane foam layer after foaming, is consistent with that in Example 1.
[0050] Comparative Example 2: The shape and structure of the antibacterial foam dressing in Comparative Example 2 are the same as those in Example 1, and the only difference is the preparation method of the composite layer. The preparation method of the composite layer in Comparative Example 2 is as follows: The first step is to prepare a 10 wt% polyurethane dimethyl sulfoxide solution; The method for preparing a 10 wt % polyurethane dimethyl sulfoxide solution is as follows: 10 g of polyurethane is taken, put into 90 g of dimethyl sulfoxide (DMSO), and stirred at 80° C. until the polyurethane is completely dissolved.
[0051] In the second step, the solution prepared in the first step is poured into a mold and a composite layer is prepared using a freeze-drying method.
[0052] Specifically, the mold is placed in a freeze dryer for directional freezing. After no liquid flows in the mold, the mold is removed, the solid is placed in the freeze dryer, the vacuum pump is turned on, and the composite layer 3 is obtained after freeze drying for 48 hours.
[0053] Comparative Example 3: The shape and structure of the antibacterial foam dressing in Comparative Example 3 are the same as those in Example 1, and the only difference is the preparation method of the composite layer. The preparation method of the composite layer in Comparative Example 3 is as follows: In the first step, 10 g of waterborne polyurethane prepolymer, 0.3 g of silicone oil, 0.2 g of N,N-dimethylcyclohexane, 0.3 g of n-pentane, and 13 g of purified water were added into a beaker, and stirred at 3000 r / min for 10 min to prepare a foaming solution.
[0054] In the second step, 13 g of isocyanate is added to the foaming solution, and stirring is continued at 1000 rpm-1200 rpm for 6 minutes. Then, it is placed in a foaming mold and kept warm at 60°C for 1 hour. After the foaming is completed, the composite layer 3 is obtained by demolding and cutting.
[0055] The electron microscope image of the vertical cross section of the composite layer prepared in Example 1 is as follows: Figure 1 The cross-sectional electron microscope image is shown in Figure 2 As shown by Figure 1It can be seen that the directional freeze-drying technology brings directional hollow channels to the polyurethane foam layer. Figure 2 It can be seen that the polyurethane foam layer still has random holes that appear in the polyurethane foam itself. The composite distribution of the vertically arranged hollow channels and random holes increases the specific surface area of the polyurethane foam layer and enhances the adsorption capacity of the polyurethane foam layer.
[0056] Experiments were conducted on the antibacterial foam dressings prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. The specific experimental steps are as follows: 1. The experimental conditions for the liquid absorption of the super absorbent fiber layer 2 are as follows: The polyurethane film layer 1, release layer 5 and medical pressure-sensitive adhesive layer 4 are removed from the antibacterial foam dressing prepared in Comparative Example 1 and Example 1, and only the super absorbent fiber layer 2 and the composite layer 3 are retained as samples. The weight W1 of the super absorbent fiber layer 2 is weighed, and the treated sample is placed in a glass dish with the composite layer 3 facing downward. Purified water is added to the dish until the liquid level reaches the middle of the composite layer 3. Purified water is added every 6 hours until the liquid level reaches the original position. The placement time is set to 6 hours, 12 hours, 18 hours, and 24 hours. After the placement time is reached, the weight W2 of the super absorbent fiber layer is weighed. The water absorption of the super absorbent fiber layer is W=W2-W1. Four groups are prepared for each of the comparative example and Example 1, and the average value is taken as the result data of the amount of liquid absorbed by the super absorbent layer. The specific results are as follows: Figure 3 shown.
[0057] Depend on Figure 3 It can be seen that the water conduction rate of the super absorbent fiber layer 2 in the foam dressing prepared in the comparative example is lower than that of the super absorbent fiber layer 2 in the foam dressing prepared in Example 1. This is because the composite layer of the foam dressing in Example 1 contains vertically arranged channels.
[0058] 2. The experimental conditions for the liquid absorption on the upper and lower surfaces of the composite layer are as follows: The composite layer in the foam dressing of Example 1 and the comparative example was taken out, and the composite layer was divided into two parts, the upper and lower parts, and the mass of each part was weighed as W3; purified water was added to the beaker, and the mass of the beaker and the purified water at this time was weighed as W4; the separated polyurethane foam layers were added to different beakers respectively, and after they were saturated and absorbed, the polyurethane foam layers were taken out, and the mass of the beaker and the purified water at this time was weighed as W5. The liquid absorption amount of the polyurethane foam layer was (W4-W5) / W3.
[0059] Depend on Figure 4 It can be seen that the liquid absorption of the lower surface of the composite layer prepared in Example 1 is increased by 7.7% compared with that in Comparative Example 1, while the liquid absorption of the upper surface is increased by 18.1 compared with that in Comparative Example 1. This proves that the composite layer prepared in Example 1 of the present invention has the advantage of large liquid absorption.
[0060] At the same time, the liquid absorption of the upper surface and the lower surface of the composite layer prepared in Example 1 are close, while the liquid absorption of the upper surface of the composite layer prepared in the comparative example is 1.9 lower than that of the lower surface. This is because the processing method of the comparative example causes the metal organic framework material to be unevenly distributed in the polyurethane foam, while the metal organic framework material in the composite layer prepared by freeze-drying method in Example 1 is uniformly distributed in the polyurethane.
[0061] 3. Experimental conditions for promoting cell growth under light conditions 100 cells were placed in a cell culture medium, the composite layer in the foam dressing of Example 1 was taken out, cut into 5 mm composite layer fragments, and the composite layer fragments were added to the culture medium to prepare six culture mediums for use; three culture mediums were cultured under light conditions, and the other three were cultured under no light conditions, and the survival of cells in the culture medium was observed every 12 hours. At the same time, a control group was set up, and the difference between the control group and the experimental group was that the composite layer prepared in Comparative Example 2 was added.
[0062] Depend on Figure 5 It can be seen that under the condition of light, the survival rate of cells is higher than that under the condition of no light. At the same time, with the increase of the use time, the survival rate of cells under the condition of no light is decreasing, while the survival rate of cells under the condition of light is increasing. By comparing the results of the experimental group with the control group, it can be proved that the composite layer prepared in Example 1 has the effect of promoting cell growth, which can prove from another perspective that the antibacterial foam dressing prepared in Example 1 has the effect of promoting wound healing.
[0063] 4. The experimental conditions for the liquid absorption of the composite layer are as follows: Take the composite layer 3 prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 as samples, weigh the mass W6 of the composite layer 3 of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively, add purified water to the beaker, weigh the mass W7 of the beaker and the purified water at this time, add the composite layer 3 to the beaker, wait for it to be saturated with water, take out the composite layer 3, weigh the mass W8 of the beaker and the purified water at this time, the liquid absorption amount per unit mass of the composite layer 3 = (W7-W8) / W6, the specific experimental results are as follows Figure 6 shown.
[0064] Depend on Figure 6It can be seen that the liquid absorption amount per unit mass of the composite layer 3 prepared in Example 1 is the largest, the liquid absorption amount per unit mass of the composite layer 3 prepared in Comparative Example 2 is the second largest, and the liquid absorption amount per unit mass of the composite layer 3 prepared in Comparative Example 3 is the lowest. This proves that the hollow channels brought by directional freezing increase the specific surface area of the polyurethane foam and improve its ability to absorb liquid. At the same time, the addition of the metal organic framework also brings a larger specific surface area to the polyurethane foam, and its ability to absorb liquid is also significantly improved. It can be seen that the combined use of metal organic framework materials and freeze drying method greatly enhances the ability of the composite layer to absorb exudate.
[0065] The preparation method of the composite layer of the present invention is the same as the preparation method of the composite layer in the antibacterial foam dressing of the present invention, and will not be described in detail here.
[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite layer, characterized in that: The polyurethane dimethyl sulfoxide solution is mixed evenly with UiO-66-(SH)2@TCPP@AgNPs powder and then freeze-dried to obtain the product, wherein the mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 400:1-100:1, the mass fraction of the polyurethane in the polyurethane dimethyl sulfoxide solution is 5%-20%, and vertical directional freezing is performed during freeze-drying.
2. A composite layer according to claim 1, characterized in that: The mass fraction of polyurethane in the dimethyl sulfoxide solution of polyurethane is 10%.
3. A composite layer according to claim 1, characterized in that: When the polyurethane dimethyl sulfoxide solution is mixed with the UiO-66-(SH)2@TCPP@AgNPs powder, the mixture is first stirred and then placed in an ultrasonic disperser for dispersion, so that the UiO-66-(SH)2@TCPP@AgNPs powder is fully dispersed.
4. A composite layer according to claim 1, characterized in that: The mass ratio of the polyurethane dimethyl sulfoxide solution to UiO-66-(SH)2@TCPP@AgNPs is 200:
1.
5. An antibacterial foam dressing, characterized in that: The invention comprises, from outside to inside, a polyurethane film layer, a composite layer, a medical pressure-sensitive adhesive layer and a release layer, wherein the composite layer is as described in any one of claims 1 to 5.
6. The antibacterial foam dressing according to claim 5, characterized in that: A super absorbent fiber layer is also arranged between the polyurethane film layer and the composite layer.
7. The antibacterial foam dressing according to claim 6, characterized in that: The thickness of the super absorbent fiber layer is 2mm-3mm.